The association between levels of tissue inhibitor of metalloproteinase-1 with acute heart failure and left ventricular dysfunction in patients with ST elevation myocardial infarction treated by primary percutaneous coronary intervention - Goldbergova, Monika Pavkova; Parenica, Jiri; Jarkovsky, Jiri; Kala, Petr; Poloczek, Martin; Manousek, Jan; Kluz, Krystyna; Kubkova, Lenka; Littnerova, Simona; Tesak, Martin; Toman, Ondrej; Pavek, Nikolas; et al. (Genetic testing and molecular biomarkers, 2012)
AIMS: Tissue inhibitors of metalloproteinase (TIMPs) bind to active matrix metalloproteinase (MMPs), and thereby inhibit their proteolytic activity. We investigated the role of polymorphisms in the gene for TIMP-1 and serum levels of TIMP-1 in association with postmyocardial infarction (MI), left ventricular (LV) dysfunction, and symptoms of acute heart failure (AHF) in patients treated with primary percutaneous coronary intervention. METHODS: In total, 556 patients with STEMI were evaluated. Levels of TIMP-1 were measured at admission and 24 h after MI onset. The TIMP-1 exon 5 SNP rs4898 (F124F with T>C) located at X chromosome was assayed. RESULTS: TIMP-1 levels were higher for men with AHF as well as for men with LV dysfunction (ejection fraction [EF]<40%). According to multivariate analysis, the TIMP-1 level was a factor with an independent negative relationship to EF and AHF in men. An independent relationship between exon 5 TIMP-1 gene polymorphism and EF, AHF or TIMP-1 level was not documented. CONCLUSION: These results provide evidence that a higher level of circulating TIMP-1 is independently associated with worse EF and AHF.
Keywords: Adult; senioři; Aged; dysfunkce levé srdeční komory; Male; lidé; lidé středního věku; Humans; Ventricular Dysfunction, Left; Percutaneous Coronary Intervention; Middle Aged; infarkt myokardu; Heart Failure; Polymorphism, Genetic; Tissue Inhibitor of Metalloproteinase-1; Myocardial Infarction; mužské pohlaví; polymorfismus genetický; dospělí; srdeční selhání; koronární angioplastika; ženské pohlaví; tkáňový inhibitor metaloproteinasy 1; Female